Perceived arrest risk, psychic rewards, and offense specialization: A partial test of rational choice theory - Thomas, Kyle J. (Criminology, 2020)
In prior tests of Beckerian rational choice theory, the notion that individuals are responsive to the (dis)incentives associated with crime has been supported. Much of this research has comprised composite scores of perceived rewards and risks of multiple, often disparate, crime types that are then used to predict “general” offending behavior. Although the results of such prior tests are informative, we believe that this tendency has resulted in two shortcomings. First, a central component of mathematical rational choice theory is overlooked, namely, that responsivity to incentives will be crime specific. That is, offenders should prefer crime types that subjectively offer greater rewards and fewer risks relative to other crimes. Second, individual differences in offending specialization are not addressed, of which Clarke and Cornish (1985) and Shover (1996) argued rational choice theories are well suited to explain. Using a sample of serious offenders, we find that in a given time period, individuals are more likely to engage in crime types they viewed as more intrinsically rewarding and less risky compared with other crimes. Furthermore, individuals displayed greater specialization in violence to the extent they view violence as more rewarding and less risky than property offenses